Heterogeneous patterns of abundance of epigeic arthropod taxa along a major elevation gradient. (29th November 2016) - Röder, Juliane; Detsch, Florian; Otte, Insa; Appelhans, Tim; Nauss, Thomas; Peters, Marcell K.; Brandl, Roland
Abstract: Species diversity is the variable most commonly studied in recent ecological research. Ecological processes, however, are driven by individuals and affected by their abundances. Understanding the variation in animal abundances along climatic gradients is important for predicting changes in ecosystem processes under global warming. High abundances make arthropods, despite their small body sizes, important actors in food webs, yet abundance distributions of major arthropod taxa along climatic gradients remain poorly documented. We sampled arthropod assemblages in disturbed and undisturbed vegetation types along an elevational gradient of 860–4550 m asl on the southern slopes of Mt. Kilimanjaro, Tanzania. In our analysis, we focused on 13 taxa of arthropods that represented three major functional groups: predators, herbivores, and decomposers. Abundance patterns were unimodal for most of the taxa and functional groups, including decomposer arthropods, and most of them peaked at low elevations in lower montane forest. When we assigned beetles to functional groups, however, decomposer beetle abundances declined almost linearly, and abundances of predator beetles ( ca . 2400 m asl) and herbivore beetles ( ca . 3000 m asl, undisturbed vegetation) peaked at higher elevations and exhibited unimodal patterns. Temperature, not primary productivity, was the best predictor of abundance for most of the taxa and groups. Disturbance was only of minor importance. Our results revealed different trends in the response of arthropod abundance along the elevational gradient that depended on the level of taxonomic and functional resolution. This highlights the need for more comparisons of different taxa along the same climatic gradients.